Experimental study of the anti-inflammatory activity of diclofenac in ultra-low doses on a model of acute carrageenan inflammation - O. A. Makhmudova; G. F. Avkhadieva; V. N. Khaziakhmetova; D. O. Nikitin; I. I. Semina (LLC "Publisher OKI", 2024)
Relevance. Drug pollution of the environment is a global environmental problem of our time. Increased consumption of medicines directly affects the level of pollution of various ecosystems, including water resources. The insufficient efficiency of existing methods for treating wastewater from drugs leads to drug pollution of water bodies and requires studying the effect of ultra-low doses of drugs on the human body and animals. A non-steroidal antiinflammatory drug, diclofenac, was detected in surface water samples in Kazan at a concentration of 1×10−9 M.The purpose of this study is to study the presence of specific pharmacological effects of diclofenac detected in water samples in ultra-low doses in experimental models of pathological processes.Methods. The experiment used 21 male white laboratory mice, which were divided into three groups (each with 7 mice). For 4 days, mice were intragastrically injected with distilled water (control group), diclofenac solution 1×10−6 M (experimental group No. 1), diclofenac solution 1×10−9 M (experimental group No. 2). On the fifth day of the experiment, inflammation was induced by injecting carrageenan lambda (1 %, Sigma) subplantarly into the right hind paw in a volume of 0.05 ml. The amount of edema was determined using an IITC Life Science plethysmometer (USA).The results of an experimental study of the specific pharmacological activity of diclofenac showed that diclofenac in ultra-low doses of 0.32×10−3 mg per 100.0 g of weight is able to reduce the severity of acute inflammation caused by subplantar injection of carrageenan and to cause NSAID-associated gastropathy in mice.Conclusion. The obtained data likely indicate a potential risk of adverse effects from drug contamination of the environment with diclofenac, even in ultra-low concentrations.